Association between Intrauterine Growth Restriction and Pregnancy Hypertension - Nada Ardilla Dwiayu Febrina; Aris Primadi; Bony Wiem Lestari (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Intrauterine Growth Restriction (IUGR) certainly poses health problems that leads to increase mortality and can cause mental and physiological disturbances to the infants. Reduced organ perfusion is one of the etiologies of IUGR which is caused by placenta obstruction. This happens because of pregnancy hypertension as a risk factor. Furthermore, educational level, employment status, parity, and anemia are also its risk factors. The objective of this study was to analyze the prevalence of IUGR and association between IUGR and pregnancy hypertension.Methods: A case control design was performed using medical records from Neonatology Department of Child Health at Dr. Hasan Sadikin General Hospital Bandung in 2012. Subjects were taken from 149 medical records of the mother who had IUGR and 149 normal birth weight infant information about the characteristics of the mothers and the infants. The data were collected and analyzed by calculating the Odds ratio (OR).Results: The prevalence of IUGR at Dr. Hasan Sadikin General Hospital in 2012 was 149 cases (4.69%). There was association between pregnancy hypertension and IUGR with OR=1.72, 95% CI (1.044–2.836).Conclusions: Pregnancy hypertension is one of the risks that generates IUGR. [AMJ.2016;3(2):212–5] DOI: 10.15850/amj.v3n2.791